PENGARUH LIKUIDITAS, SOLVABILITAS, AKTIVITAS PROFITABILITAS, DAN SKALA PERUSAHAAN TERHADAP NILAI PERUSAHAAN [THE EFFECT OF LIQUIDITY, SOLVENCY, PROFITABILITY ACTIVITIES, AND COMPANY SCALE ON COMPANY VALUE] - Suparmoko, Yuphi Handoko (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2024)
The company's main objective is to maximize shareholder value by increasing the rate of return on investments made. Company value can be measured by the amount of price to book value (PBV). A high price to book value is the desire of company owners because a high price to book value indicates high prosperity and welfare of shareholders. The company value is used by shareholders in determining which shares to buy. The aim of this research is to determine the effect of current ratio, debt to equity ratio, firm size, total asset turnover, and return on assets on company value. The population in the research was 11 companies and 8 Public Companies in the Pharmaceutical Sub Sector on the Indonesia Stock Exchange for the 2015-2019 period. The analytical method used is simple linear regression using SPSS version 19 with the stepwise method. The research results show that firm size has a significant effect on company value, while the current ratio, debt to equity ratio, total asset turnover, and return on assets have no effect on company value.